Paying the Toll in Nuclear Reprogramming - Liu, Chun; Himmati, Farhan; Sayed, Nazish (Frontiers in Cell and Developmental Biology, 2017)
The ability to reverse lineage-committed cells towards pluripotent stem cells or to another cell type is one of the ultimate goals in regenerative medicine. We recently discovered that activation of innate immunity, through Toll-like receptor 3, is required during this conversion of cell fate by causing global changes in the expression and activity of epigenetic modifiers. Here we discuss, in a comprehensive manner, the recent studies on the role of innate immunity in nuclear reprogramming and transdifferentiation, the underlying mechanisms, and its role in regenerative medicine.